Lenz–Majewski syndrome in a patient from Egypt. Issue 10 (12th August 2019) - Afifi, Hanan H.; Abdel‐Hamid, Mohamed S.; Mehrez, Mennat I.; El‐Kamah, Ghada; Abdel‐Salam, Ghada M. H.
Abstract: Lenz–Majewski syndrome (LMS) is an extremely rare type of cutis laxa caused by dominant mutations in PTDSS1 gene. We report an Egyptian patient who presented with cutis laxa, brachydactyly, and progeroid features. LMS syndrome was suspected and a previously reported de novo heterozygous missense mutation (c.284G > T, p.R95L) in PTDSS1 was identified. To the best of our knowledge, nine molecularly proven patients with LMS from different ethnicities have been reported. Our patient is the first report from the Middle East and the tenth molecularly proven patient reported to date. His clinical features were in accordance with LMS syndrome. In addition, his hands X‐ray images showed hypoplastic or absent middle and proximal phalanges but sparing the thumbs. This hand patterning was similarly observed before. Further, he had relatively large and convex fingernails. Our report highlights this unique hand patterning and suggests these signs should be considered among the diagnostic criteria of LMS. Further reports of patients with PTDSS1 mutations are necessary to further elucidate the detailed clinical features of LMS syndrome.